2019
DOI: 10.5194/acp-2019-540
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of SO<sub>2</sub> on optical properties of secondary organic aerosol generated from photooxidation of toluene under different relative humidity

Abstract: <p><strong>Abstract.</strong> Secondary organic aerosol (SOA) have great impacts on air quality, climate change and human health. The composition and physicochemical properties of SOA differ a lot for they originated under different atmospheric conditions and from various precursors and oxidations. In this work, photooxidation experiments of toluene were performed under four conditions (dry, dry with SO<sub>2</sub>, wet, and wet with SO&… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…CHNOS molecules with S/C less than 0.04 were the dominant contributors to b abs (CHNOS), whereas those with S/C higher than 0.04 (molecules with two or more sulfate functional groups) tended to have limited contributions to BrC absorption. Compared with N‐containing functional groups, the addition of S‐containing functional groups tended to weaken Mb abs of CHNOS, which is consistent with results of quantum chemical calculations (Nakayama et al, 2015) and smog chamber experiments (Zhang et al, 2019). Such a phenomenon is probably because sulfate‐containing groups are not chromophoric and rather have a hypochromic effect on the molecule (Moise et al, 2015; Nguyen et al, 2012).…”
Section: Resultssupporting
confidence: 86%
“…CHNOS molecules with S/C less than 0.04 were the dominant contributors to b abs (CHNOS), whereas those with S/C higher than 0.04 (molecules with two or more sulfate functional groups) tended to have limited contributions to BrC absorption. Compared with N‐containing functional groups, the addition of S‐containing functional groups tended to weaken Mb abs of CHNOS, which is consistent with results of quantum chemical calculations (Nakayama et al, 2015) and smog chamber experiments (Zhang et al, 2019). Such a phenomenon is probably because sulfate‐containing groups are not chromophoric and rather have a hypochromic effect on the molecule (Moise et al, 2015; Nguyen et al, 2012).…”
Section: Resultssupporting
confidence: 86%
“…A series of photochemical simulation experiments of hydrocarbons and NOx were designed and conducted according to the atmospheric conditions in Lanzhou and Beijing (Zhang and Li, 1998). Then a serious environmental issues were studied based on the smog chambers constructed with various size in the past decades, including the mechanism of photochemical reaction (Liu et al, 2017;Wang et al, 2014;Wu et al, 2007), ozone and SOA formation (Li et al, 2018a;Ma et al, 2018;Wang et al, 2015), biomass burning reactions (Zhang et al, 2011), the photochemical process of the gasoline and diesel (Chen et al, 2019a;Chen et al, 2019b;Kamens et al, 2011), physicochemical properties of SOA formed under various conditions (Li et al, 2017a;Li et al, 2020;Li et al, 2018b;Peng et al, 2018;Zhang et al, 2020), et al However, most of the chambers constructed in China were indoor smog chambers, establishment large-scale outdoor smog chambers in China was limited. In order to study the atmospheric pollution process close to China's actual atmospheric environment, it was necessary to build a large outdoor smog chamber in China.…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory studies demonstrated that the presence of SO 2 could enhance the SOA formation from anthropogenic and biogenic precursors, e.g. monoterpenes, isoprene, aromatics (Liggio and Li, 2013;Santiago et al, 2012;Kleindienst et al, 2006;Zhang et al, 2020;Yang et al, 2020;Liu et al, 2019). In addition, the presence of SO 2 could affect the light scattering and absorption properties of formed SOA (Zhang et al, 2020;Jaoui et al, 2008;Nakayama et al, 2015Nakayama et al, , 2018.…”
Section: Introductionmentioning
confidence: 99%
“…monoterpenes, isoprene, aromatics (Liggio and Li, 2013;Santiago et al, 2012;Kleindienst et al, 2006;Zhang et al, 2020;Yang et al, 2020;Liu et al, 2019). In addition, the presence of SO 2 could affect the light scattering and absorption properties of formed SOA (Zhang et al, 2020;Jaoui et al, 2008;Nakayama et al, 2015Nakayama et al, , 2018. It should be noted that most of the previous studies focused on the effect of SO 2 on the particle formation from a single precursor.…”
Section: Introductionmentioning
confidence: 99%